Thucydides and Hesiod - Finglass, P.J. (Fabrizio Serra editore, 2013)
The puzzling reference by Thucydides, during his account of Demosthenes’ Aetolian campaign in 426, to the death of Hesiod, can be explained as an instance of foreshadowing through myth: Hesiod’s tragic end prepares the reader for the tragic consequences of Demosthenes’ decisions. A similar use of mythical foreshadowing in Herodotus is compared.